Keeping autocrats at bay: lessons from South Korea and Taiwan - Croissant, Aurel; Kim, Jung-eun (Global Asia, 2020)
They offer differing perspectives in the struggle to entrench democratic norms of governance in a political environment where autocratic tendencies persist.